Liability of the Directors Cause Not Implementing the Principle of Prudence in Distributing Mudharabah - Rajaingat Saragih; Rony Andre Christian Naldo (Jurnal Ilmiah Advokasi, 2023)
Directors is the organ that represents the sharia bank in carrying out sharia banking business activities, one of which is the distribution of mudharabah financing. Before distributing mudharabah financing to prospective customers who receive the facility, in accordance with the provisions of Article 2 and Article 29 verse (2) of Law Number 10 of 1998 jo. Article 2 and Article 35 verse (1) of Law Number 21 of 2008, Directors representing sharia banks, are obliged to apply the principle of prudence.This research discusses the obligation of Directors representing sharia bank to apply the principle of prudence before distributing mudharabah financing to prospective customers who receive the facility. In this regard, this research is focused on examining the liability of Directors cause not implementing the principle of prudence in distributing mudharabah financing to customers who receive facilities, which resulted in a decline in the health level of sharia bank.This research is prescriptive, using normative juridical methods, with using a statutory approach, and a conceptual approach. The type of data used is secondary data.The results of this research conclude that the liability of Directors for failure to apply the principle of prudence in distributing mudharabah financing to customers who receive facilities which results in a decline in the health level of sharia bank is that sanctions can be applied to Directors in the realm of Civil Law, the application of which does not reduce the application of sanctions in the realm of Penal Law.Key Words: Liability, Director, Prudence